Seizure Classification From EEG Signals Using an Online Selective Transfer TSK Fuzzy Classifier With Joint Distribution Adaption and Manifold Regularization - Zhang, Yuanpeng; Zhou, Ziyuan; Bai, Heming; Liu, Wei; Wang, Li (Frontiers in Neuroscience, 2020)
To recognize abnormal EEG signals for epileptics, in this study, we proposed an online selective transfer TSK fuzzy classifier underlying joint distribution adaption and manifold regularization. Compared with most of the existing transfer classifiers, our classifier has its own characteristics: 1) The labeled EEG epochs from the source domain cannot accurately represent the primary EEG epochs in the target domain. Our classifier can make use of very few calibration data in the target domain to induce the target predictive function. 2) A joint distribution adaption is used to minimize the marginal distribution distance and the conditional distribution distance between the source domain and the target domain. 3) Clustering techniques are used to select source domains so that computational complexity of our classifier is reduced. We construct 6 transfer scenarios based on the original EEG signals provided by the Bonn University to verify the performance of our classifier and introduce 4 baselines and a transfer SVM for benchmarking studies. Experimental results indicate that our classifier wins the best performance and is not very sensitive to its parameters.